Building Character Of Bugis Community In Bone From The Perspective Of Quran And Local Wisdom - Muhammad Yusuf; Nahdhiyah Nahdhiyah; Kamaluddin Nurdin Marjuni (Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2024)
Volume: 24 No : 2 (page: 193-220)